2015
DOI: 10.1038/jp.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum markers, characteristics and morbidly adherent placenta in women with previa

Abstract: Elevated PAPP-A, elevated MS-AFP and prior CDs are associated with MAP among women with previa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
3
35
2
2
Order By: Relevance
“…Our results are consistent with the previous studies indicating that elevated second trimester MS‐AFP levels are associated with MAP among women with placenta previa [7–9,12]. However, they particularly evaluated the association of significantly elevated MS‐AFP levels (> 2.5 MoM, higher than the cut‐off value for the upper limit of normal in second trimester screening) and suggested that this value can be used to predict the occurrence of placenta accreta [8–10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with the previous studies indicating that elevated second trimester MS‐AFP levels are associated with MAP among women with placenta previa [7–9,12]. However, they particularly evaluated the association of significantly elevated MS‐AFP levels (> 2.5 MoM, higher than the cut‐off value for the upper limit of normal in second trimester screening) and suggested that this value can be used to predict the occurrence of placenta accreta [8–10].…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of the previous reports, elevated maternal serum alphafetoprotein (MS‐AFP) and human chorionic gonadotropin (hCG) have a relation with the increased risk of placenta accreta [7–10]. Besides, two recent retrospective studies revealed increased levels of pregnancy‐associated plasma protein‐A (PAPP‐A) among women with placenta accreta [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This comes in agreement with the opinion of some other authors [23][24][25].The elevated levels of MSAFP in cases of pathologically adherent placenta could be explained by a disruption of the maternal-fetal-placental barrier, placental vascular damage, feto-maternal bleeding or relative placental ischemia [23,24]. Despite many authors studied and proved elevated level of MSAFP and its association with morbid placental adherence among women with placenta previa [6,9,25] and some used it as a predictor for pregnancy outcome, but they used it earlier in the second trimester. Our results come consistent to this finding but we investigated our patients in the third trimester owing to authorize admission of participants and avoiding dropping ones during the research time.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have proven that important risk factors included prior cesarean deliveries, placenta previa, prior uterine surgery or curettage, advanced maternal age, and multiparity [4,5]. On the other hand, entities examined for predicting abnormal invasion of placenta were the maternal serum biological markers in first and second trimesters namely, elevated maternal serum alpha-fetoprotein (MSAFP), human chorionic gonadotropin (hCG) and pregnancy-associated plasma protein-A (PAPP-A) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…But when placental necrosis happens, the separation of placenta and uterus leads to barrier leak, which will increase the amount of AFP delivered from the fetus to the mother. Studies have demonstrated that maternal serum AFP is clinically elevated in cases of a morbidly adherent placenta, and it is a secondary indicator of placenta previa[ 6 - 8 ]. However, until now there have been no reports emphasizing its relationship with the degree of placental damage (such as hematoma necrosis).…”
Section: Discussionmentioning
confidence: 99%